Comparison of low-density lipoprotein cholesterol equations in patients with dyslipidaemia receiving cholesterol ester transfer protein inhibition. (3rd October 2022) - Martin, S; Ditmarsch, M; Simmons, M; Alp, N; Turner, T; Davidson, M; Kastelein, J J P
Abstract: Background: Low-density lipoprotein (LDL-C) lowering is imperative in cardiovascular disease prevention. Effectively translating the evidence for LDL-C lowering to maximize clinical and public health benefits depends on the availability of accurate LDL-C results from clinical laboratories to guide therapy. Furthermore, prior work has raised the possibility that cholesterol esterase transfer protein (CETP) inhibition could interfere with accurate assessment of LDL-C. Purpose: We aimed to compare accuracy of three clinically implemented LDL-C equations in a clinical trial of CETP inhibition. Methods: Men and women aged 18–75 years with dyslipidaemia were recruited from 17 sites in the Netherlands and Denmark. Patients were randomly assigned to one of nine groups using various combinations of the CETP inhibitor TA-8995, statin therapy, and placebo. In pooled measurements over 12 weeks, we calculated LDL-C by the Friedewald, Martin/Hopkins, and Sampson equations, and compared values with preparative ultracentrifugation (PUC) LDL-C as the reference measure (also known as "beta quantification"). Based on prior literature and dyslipidaemia guidelines, we examined correct classifications across the LDL-C 1.81 mmol/L cutpoint in the subgroup of patients with triglycerides of 1.69–4.51 mmol/L. Results: The analysis included 242 patients contributing 921 observations. The full distributions of differences between LDL-C estimates and PUC are shown in Figure 1. Overall median LDL-C differences between estimates and PUC were small: Friedewald, 0.00 (25th, 75th: −0.10, 0.08) mmol/L; Martin/Hopkins, 0.02 (−0.08, 0.10) mmol/L; and Sampson, 0.05 (−0.03, 0.15) mmol/L. In the subgroup with estimated LDL-C <1.81 mmol/L and triglycerides 1.69–4.51 mmol/L, the Friedewald equation underestimated LDL-C with a median difference versus PUC of −0.25 (−0.33, −0.10) mmol/L, whereas the Martin/Hopkins equation corrected this issue with a median difference of 0.00 (−0.08, 0.10) mmol/L and the Sampson equation showed tendency towards underestimation with a median difference of −0.06 (−0.13, 0.00) mmol/L. In patients with triglyceride levels of 1.69–4.51 mmol/L, Figure 2 shows the proportion of LDL-C levels classified by the equations as < or ≥1.81 mmol/L that were correctly classified when compared with PUC. All three equations showed >95% accuracy when estimated LDL-C levels were ≥1.81 mmol/L. However, the proportion of LDL-C observations <1.81 mmol/L that were correctly classified compared with PUC was 71.4% by Friedewald versus 100.0% by Martin/Hopkins and 93.1% by Sampson. Conclusion: In Europeans with dyslipidaemia, our analysis shows improved accuracy in LDL-C when using contemporary LDL-C equations over the Friedewald equation, particularly when using the Martin/Hopkins equation. High levels of accuracy with the Martin/Hopkins equation were seen in individuals treated with CETP inhibition and even in the context of low LDL-C and high triglyceride levels. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Dezima and NewAmsterdam Pharma